Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1680/stbu.2009.162.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Perforation owing to impacts on reinforced concrete slabs

Abstract: The development and testing of a finite-element model to investigate the impact resistance of reinforced concrete slabs, with and without metal decking, is described. The model is validated against empirical design formulae for cylindrical projectiles. A series of experimental tests involving I-sections impacting reinforced concrete slabs is described and the results are used to validate the model further. Having validated the model, it is then used to provide data for impacts of the slab by typical column sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Fig. 1 shows the relationship between the penetration depth (x exp ) and velocity of the impactor at the time of contact for the impact test data [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In general, it was observed that with the increase in the velocity of the impacting object the penetration depth exhibited by the specimens also increases.…”
Section: Critical Review Of the Published Experimental Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Fig. 1 shows the relationship between the penetration depth (x exp ) and velocity of the impactor at the time of contact for the impact test data [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In general, it was observed that with the increase in the velocity of the impacting object the penetration depth exhibited by the specimens also increases.…”
Section: Critical Review Of the Published Experimental Studiesmentioning
confidence: 95%
“…Based on the velocity of impacting objects, the loading intensities generated due to the above abnormal activities can be classified as high or low-velocity impacts. Several experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] studies have been conducted to study the response of the RC slabs under high loading rates, however, the focus of most of these studies was to investigate the influence of the high-velocity projectiles penetrating the RC slabs to ensure a certain level of resilience required in the nuclear and military structures. As a result, the focus of these studies was to examine the required thickness to prevent penetration, perforation and scabbing.…”
Section: Introductionmentioning
confidence: 99%
“…The test is relevant to the design of civil infrastructure where concrete structural elements, such as concrete slabs, are often subjected to drop of heavy weights (e.g. steel elements) during the construction operations of multi-story buildings (Algaard et al 2005;Izatt et al 2009). In addition, polymer concrete pipes may drop resulting in impact loading during the transportation and installation of pipelines.…”
Section: Testing Methodsmentioning
confidence: 99%
“…Equation (2) corresponds to the state of the water by the shock compression; Formula (3) corresponds to the expansion of water state by impacted. In Two equations, for the density of the material; c for the curves intercept the vertical axis;…”
Section: B Explosive Materials Modelmentioning
confidence: 99%